Teaching and Learning in the 21st Century: Integrating Technology and Pedagogical Innovations - Rina Kusuma; Ahmad Fauzi (Yayasan Azhar Amanaa Yogyakarta, 2025)
This research explores the integration of critical thinking skills into educational curricula to meet 21st-century social and economic demands. Critical thinking empowers students to analyze information, make informed decisions, and solve problems creatively, making it vital in modern education. The study reviews practices in Finland, Singapore, and Canada, focusing on student-centered methods like inquiry-based learning and collaborative activities that enhance cognitive skills and academic performance. However, challenges include inconsistent teaching, varied assessments, and inadequate teacher training. A qualitative approach was used, employing case studies and comparative analysis of Finland, Singapore, and Canada’s educational systems. Data were collected through interviews with educators, surveys of students and parents, and curriculum analysis. Findings emphasize the need for standardized critical thinking education, clear assessment frameworks, and more educator support to optimize implementation, enhancing student engagement, academic success, and lifelong learning. Future research should explore long-term impacts and best practices to ensure equitable access to critical thinking education.